1993
DOI: 10.1172/jci116288
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine-acylcarnitine translocase deficiency with severe hypoglycemia and auriculo ventricular block. Translocase assay in permeabilized fibroblasts.

Abstract: Deficiency of the enzymes of mitochondrial fatty acid oxidation and related carnitine dependent steps have been shown to be one of the causes of the fasting-induced hypoketotic hypoglycemia. We describe here carnitine-acylcarnitine translocase deficiency in a neonate who died eight days after birth. The proband showed severe fasting-induced hypoketotic hypoglycemia, high plasma creatine kinase, heartbeat disorder, hypothermia, and hyperammonemia. The plasma-free carnitine on day three was only 3 ,M, and 92% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 23 publications
3
49
0
Order By: Relevance
“…Thirty-one articles describing clinical reports of CACT deficiency were found by searching the PubMed database (Al Aqeel et al 2003;Al-Sannaa and Cheriyan 2010;Brivet et al 1996;Chalmers et al 1997;Costa et al 1999;Costa et al 2003;Fearing et al 2011;Fukushima et al 2013;Galron et al 2004;Geven et al 2007;Huizing et al 1997Huizing et al , 1998Iacobazzi et al 2004a;Iacobazzi et al 2004b;Korman et al 2006;Lee et al 2007;Lopriore et al 2001;Morris et al 1998;Niezen-Koning et al 1995;Nuoffer et al 2000;Ogawa et al 2000;Ogier de Baulny et al 1995;Olpin et al 1997;Pande et al 1993;Parini et al 1999;Pierre et al 2007;Roschinger et al 2000;Rubio-Gozalbo et al 2003;RubioGozalbo et al 2004;Stanley et al 1992;Wang et al 2011;Yang et al 2001). Data from the literature were compiled, compared with the cases reported here, and discussed.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one articles describing clinical reports of CACT deficiency were found by searching the PubMed database (Al Aqeel et al 2003;Al-Sannaa and Cheriyan 2010;Brivet et al 1996;Chalmers et al 1997;Costa et al 1999;Costa et al 2003;Fearing et al 2011;Fukushima et al 2013;Galron et al 2004;Geven et al 2007;Huizing et al 1997Huizing et al , 1998Iacobazzi et al 2004a;Iacobazzi et al 2004b;Korman et al 2006;Lee et al 2007;Lopriore et al 2001;Morris et al 1998;Niezen-Koning et al 1995;Nuoffer et al 2000;Ogawa et al 2000;Ogier de Baulny et al 1995;Olpin et al 1997;Pande et al 1993;Parini et al 1999;Pierre et al 2007;Roschinger et al 2000;Rubio-Gozalbo et al 2003;RubioGozalbo et al 2004;Stanley et al 1992;Wang et al 2011;Yang et al 2001). Data from the literature were compiled, compared with the cases reported here, and discussed.…”
Section: Resultsmentioning
confidence: 99%
“…Rare case reports noticed conduction anomalies or ventricular arrhythmias as a major feature of these defects. Pande et al 9 reported the first case of carnitineacylcarnitine translocase deficiency in a newborn infant with severe hypoglycemia and atrioventricular block (patient 1, Table). de Lonlay-Debeney et al 19 reported the case of a 9-month-old child with VLCAD deficiency who presented with severe heart failure and polymorphic ventricular tachycardia masquerading as fulminant myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, arrhythmias and conduction defects, in association with hepatomuscular symptoms, have been previously mentioned in isolated cases of fatty acid oxidation disorders. 9 Severe ventricular arrhythmias are suspected as the cause of sudden infant death syndrome or unexpected death in young children harboring these defects. 10,11 Although neonatal ventricular or atrial tachycardias in infants with a structurally and functionally normal heart are usually considered idiopathic, we report a series of 24 children in whom arrhythmias or conduction defects were the predominant presenting symptom of various fatty acid oxidation disorders.…”
mentioning
confidence: 99%
“…In some experiments, the culture medium was supplemented with 5 mM DCA for 3 d before plating and throughout the 48-h period of cell culture in the 25-cm 2 flasks. Cells were incubated with 14 C-labeled substrates for 45 min at 37°C, in 1 mL of respiratory medium (225 mM mannitol, 25 mM HEPES, 50 M EDTA (pH 7.5), 5 mM potassium phosphate, 3 mM ADP) supplemented with 2 mg/mL BSA and 20 g/mL digitonin (20). The production of 14 Figure 1.…”
Section: Case Reportsmentioning
confidence: 99%